GLOBALISATION AND STRATEGY: “NEGARA, TERITORI DAN KEDAULATAN DI ERA GLOBALISASI” - Indra Kusumawardhana; Zulkarnain (Universitas Nasional, 2016)
The development of Globalization in this century is far more interesting for so many academias. The main issue that becomes the area of debate is the impact of Globalization to the concept of Nation-State, territory and sovereignty (Wesphalian System). The group of skeptic thinker assume that globalization bring a negative impact to Nation-State, territory and sovereignty. In the other hand, those who put their faith in globalization argue that globalization is inevitable. Therefore, an action of reconfiguration is needed to control the shift of every aspect in the context of world politics. For the sake of this need, Nation-State needs to be strengthening in order to retain its existence and legitimation. The arguments of this paper tend to pro the second position as the staple of this paper. The nature of relationship between Globalization and Nation-State is continuous and dynamic. Therefore, reconfiguration is needed if we want to have a better understanding for the concept of Nation-State, territory, and sovereignty.